Reasons and pattern of tooth extraction in International Islamic University Malaysia, Kulliyyah of Dentistry Polyclinic - Muhammad Ali, Suhaila; Mustafa, Nazih Shaban; Kashmoola, Muhannad Ali; Tin, Myo Han (Elsevier Ltd, 2019)
Objective: To investigate the reasons and pattern of tooth extraction among patients attending International Islamic University Malaysia, Kulliyyah of Dentistry Polyclinic. Materials and Methods: This is a retrospective study. The patient’s age, gender, race and reason for tooth extraction were recorded. Result: A total 1,036 teeth were extracted. Caries was the main reasons for 53.3% of extractions. The highest number of extraction was observed at age of 21 to 40 years old (44.4%) Females had 56.6%. Malay showed highest extraction case, 85.2%. Conclusion: Dental caries is the main reason for tooth extraction among patients attending IIUM Kulliyyah of Dentistry Polyclinic.